Design of a Glass Bottom Catamaran as a Tourist Attraction on Aceh's Banyak Island - Deddy Chrismianto; Ahmad Firdhaus; Hassan Al Muhshi; Kiryanto Kiryanto (Diponegoro University, 2024)
Aceh's Banyak Island Due to its large water areas and fascinating islands that retain the grandeur of its sea and beaches, Singkil has risen as a new star in the world of tourism. Nonetheless, traditional fishing boats remain the principal mode of transportation for visitors in the region. The Glass Bottom Catamaran has been launched as a novel and attractive approach to admire the natural beauty of the seas around Banyak Island to capitalize on Indonesia's maritime tourist potential. The design process for this vessel involves basic linear regression calculations, the formulation of the ship's lines plan, the design of the vessel's General Arrangement, and the creation of a 3D model utilizing software. Stability calculations follow IMO standards, resistance calculations follow the Slender Body approach, and motion analysis follows Nordfork 1987 norms. As a result, the vessel's primary dimensions are as follows: LOA = 20.25 m, B = 7.04 m, B1 = 1.8 m, H = 2.4 m, T = 1.55 m, Vs = 17 knots, and a total passenger capacity of 54 people. In this investigation, the resistance value is 42.3 kN, concerning its ability to transport 60 tons at 17 knots. The stability study fulfils IMO guidelines, while the motion analysis meets Nordfork 1987 norms